Respuesta :
Answer:
Option C is right answer.
Step-by-step explanation:
Given two equations as
2y + 4x = 18
2y – 3x = 4
We have to use substitution method.
From first equation find the value of y.
2y = 18-4x
Or y = 9-2x
Substitute this in II equation.
2(9-2x)-3x =4
18-4x-3x =4
-7x = 4-18 = -14
Divide by -7
x =2
Since y = 9-2x, substitute x=2 to get y
y = 9-2(2) = 5
Answer is (2,5)
To verify:
Substitute (2,5) in the given two equations to check.
2(5)+4(2) = 18 is right
2(5)-3(2) = 4 is also right.
Hence solution is (2,5)